Adsorption Behavior of Pb, Cd, Ca, Al, Zn And Co Metal Ions on Cation Exchange Resin Dowex 50 Wx8 (Nh4+ Form) From Aqueous Acetone-Ammonium Propionate Media - Kamble S, Rajan (International Journal of Scientific Research and Management (IJSRM), 2021)
There has a wide interest in stability of different types of ion exchange resins against ionizing radiations. The irradiation damage and stability of polystyrendigni benzene and phenolformaldehide sulphonic acid ion exchange resins was investigated by determination of the radiolytic gases. The gas analysis showed a very good linear dose dependence of the evolved hydrogen and carbon monoxide. The linearity of carbon dioxide was good for Dowex 50 WX 10 but less pronounce for zeo-carb 215. Sulphur dioxide was at least partially produced by direct action and was consumed by secondary reaction during irradiation. Kuzin  et al [1] analysed radiolytic gases evolved from a carboxylic acid exchange resin. Wiely et al [2] investigated gamma radiation induce degradation of sulphonetic styrle resin cross link with 4 and 8 % m / p dinyl benzene isomer or mixtures thereof including commercial divenyle benzene have been shown loss in capacity 5-12. 8% at the radiation intensities of 290 R/hr and total dose 0.91 – 1.0 x 10-8 rad in presence of water.